Effect of photon induced photoacoustic streaming (PIPS) on bond strength to dentine of two root canal filling materials. Issue 10 (2nd June 2016) - Miletić, Ivana; Chieffi, Nicoletta; Rengo, Carlo; Ferrari, Marco; Nathanson, Dan; Baraba, Anja
Abstract : Objectives: The aim of this study was to evaluate the effect of photon induced photoacoustic streaming (PIPS) technique in combination with EDTA on bond strength of gutta‐percha/AH Plus and Resilon/RealSeal SE root canal fillings to root dentine. Materials and Methods: Forty freshly extracted human maxillary anterior teeth with intact straight roots, were instrumented endodontically with rotating ProTaper instruments and randomly divided into two experimental groups. In group 1 ( n  = 20), root canals were rinsed for 1 minute with 2 ml of 17% EDTA. In group 2 ( n  = 20), Er:YAG laser, with a 14 mm long 400 μ diameter tapered PIPS tip, was used for 1 minute with 2 ml of 17% EDTA. The laser parameters used were: 20 mJ per pulse, 15 Hz, 50 microsecond. In each experimental group, half of the root canals ( n  = 10) were obturated with gutta‐percha/AH Plus and other half ( n  = 10) with Resilon/RealSeal SE. A micropush‐out test was performed on sectiond specimens of the filled roots using a universal testing machine and resistance to failure plus failure modes were determined. Results: Both gutta‐percha/AH Plus groups had higher bond strength to root dentin than the Resilon/RealSeal SE groups ( P  < 0.05). The smear layer removal protocol, with EDTA only or combining PIPS technique with EDTA, had no influence on bond strength of either gutta‐percha/AH Plus, or Resilon/RealSeal SE ( P  > 0.05). Conclusion: Within the limitations of this study, it was found that the application of the PIPS technique did not have an affect on the push‐out bond strength of Resilon/RealSeal SE root canal filling to dentin nor on the gutta‐percha/AH Plus. A significant difference in bond strength was noted between the two root canal filling materials. Lasers Surg. Med. 48:951–954, 2016. © 2016 Wiley Periodicals, Inc.